Pengaruh Kepuasan Pelanggan Terhadap Minat Penggunaan Ulang (Survey Pada Pengguna E-Wallet Shopeepay) - Trania Maharani; Sindiani Fatimah; Abdul Yusuf (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to analyze the effect of customer satisfaction on reuse interests. This analysis uses an independent variable i.e. customer satisfaction. The dependent variable are interest in reuse. The research methods used in this research are quantitative research methods. The population in this study was ShopeePay users, with a sample of 100 respondents. Sample withdrawal techniques are used random sampling. The data collection techniques used in this study are primary data and secondary data. This research was conducted with the help of spss 25 for windows application. The data analysis technique used is simple linear regression analysis. The results stated that there was a positive and significant influence on customer satisfaction on the interest in reuse in ShopeePay e-wallets. It shows that the effect of reuse interest on customer satisfaction is 74%, and 26% of customer satisfaction is influenced by other variables.